Anthocyanin metabolic engineering of Euphorbia pulcherrima: advances and perspectives - Lozoya-Gloria, Edmundo; Cuéllar-González, Fernando; Ochoa-Alejo, Neftalí (Frontiers in Plant Science, 2023)
The range of floral colors is determined by the type of plant pigment accumulated by the plant. Anthocyanins are the most common flavonoid pigments in angiosperms; they provide a wide range of visible colors from red-magenta to blue-purple, products of cyanidin and delphinidin biosynthesis, respectively. For the floriculture industry, floral color is one of the most important ornamental characteristics for the development of new commercial varieties; however, most plant species are restricted to a certain color spectrum, limited by their own genetics. In fact, many ornamental crops lack bluish varieties due to the lack of activity of essential biosynthetic enzymes for the accumulation of delphinidin. An example is the poinsettia (Euphorbia pulcherrima Willd. ex Klotzsch), the ornamental plant symbol of Christmas and native to Mexico. Its popularity is the result of the variety of colors displayed by its bracts, a kind of modified leaves that accumulate reddish pigments based mainly on cyanidin and, to a lesser extent, on pelargonidin. The commercial success of this plant lies in the development of new varieties and, although consumers like the typical red color, they are also looking for poinsettias with new and innovative colors. Previous research has demonstrated the possibility of manipulating flower color through metabolic engineering of the anthocyanin biosynthesis pathway and plant tissue culture in different ornamental plant species. For example, transgenic cultivars of flowers such as roses, carnations or chrysanthemums owe their attractive bluish colors to a high and exclusive accumulation of delphinidin. Here, we discuss the possibilities of genetic engineering of the anthocyanin biosynthetic pathway in E. pulcherrima through the introduction of one or more foreign delphinidin biosynthetic genes under the transcriptional control of a pathway-specific promoter, and the genome editing possibilities as an alternative tool to modify the color of the bracts. In addition, some other approaches such as the appropriate selection of the cultivars that presented the most suitable intracellular conditions to accumulate delphinidin, as well as the incorporation of genes encoding anthocyanin-modifying enzymes or transcription factors to favor the bluish pigmentation of the flowers are also revised.